Real time monitoring of risk-adjusted paediatric cardiac surgery outcomes using variable life-adjusted display: implementation in three UK centres. Issue 19 (5th April 2013) - Pagel, Christina; Utley, Martin; Crowe, Sonya; Witter, Thomas; Anderson, David; Samson, Ray; McLean, Andrew; Banks, Victoria; Tsang, Victor; Brown, Katherine
Abstract : Objective: To implement routine in-house monitoring of risk-adjusted 30-day mortality following paediatric cardiac surgery. Design: Collaborative monitoring software development and implementation in three specialist centres. Patients and methods: Analyses incorporated 2 years of data routinely audited by the National Institute of Cardiac Outcomes Research (NICOR). Exclusion criteria were patients over 16 or undergoing non-cardiac or only catheter procedures. We applied the partial risk adjustment in surgery (PRAiS) risk model for death within 30 days following surgery and generated variable life-adjusted display (VLAD) charts for each centre. These were shared with each clinical team and feedback was sought. Results: Participating centres were Great Ormond Street Hospital, Evelina Children's Hospital and The Royal Hospital for Sick Children in Glasgow. Data captured all procedures performed between 1 January 2010 and 31 December 2011. This incorporated 2490 30-day episodes of care, 66 of which were associated with a death within 30 days.The VLAD charts generated for each centre displayed trends in outcomes benchmarked to recent national outcomes. All centres ended the 2-year period within four deaths from what would be expected. The VLAD charts were shared in multidisciplinary meetings and clinical teams reported that they were a useful addition to existing quality assurance initiatives. Each centre is continuing to use the prototype software to monitor their in-house surgical outcomes. Conclusions: Timely and routine monitoring of risk-adjusted mortality following paediatric cardiac surgery is feasible. Close liaison with hospital data managers as well as clinicians was crucial to the success of the project.